Design e Ergonomia per la Human-Robot Interaction Strategie e strumenti Human-Centred Design per la collaborazione trans-disciplinare e per la progettazione dell'accettabilità delle nuove tecnologie robotiche - BECCHIMANZI, CLAUDIA (Serie di architettura e design, 2022)
This book investigates the relationship between design (specifically, the Human-Centred Design, Interaction Design and User Experience approaches) and the complex area of Human-Robot Interaction (specifically, social robotics for care). The research begins by framing the scientific problem of demographic aging and the increasing diffusion of wearable and robotic technologies for assisting and supporting the well-being and independence of the elderly and frail. Then, the research examines the role, contributions, and challenges of design in relation to the issue of acceptability in robotics, both from a theoretical-epistemological as well as from a practical-applicative viewpoint. The book, therefore, investigates methods and tools for implementing cross-disciplinary collaboration and for designing acceptability and interaction with new technologies in order to improve the quality of life and psychophysical health of human beings. The overall goal of the of the research presented in this volume is to bridge the gap between the two scientific areas of design and robotics, and let them converge in order to design assistive and social robots that can be effectively accepted as well as appropriate for people's specific needs. This is made possible through the development of a connection between the methodological approaches and tools of both disciplines in order to structure a framework for: cross-disciplinary collaboration and management of development processes in robotics research projects and design; and the application of the iterative process peculiar of HCD to robotics. On this basis, the research output was developed, namely the operational tool "Robotics & Design: the tool to design Human-Centered Assistive Robotics" which can be found at the link: www.roboticsdesign.org.